2022
DOI: 10.1021/acsomega.2c03089
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Deposition of Nanostructured CsPbBr3 Perovskite Quantum Dot Films on Mesoporous TiO2 and Their Enhanced Visible-Light Photodegradation Properties

Abstract: Herein, we report the in situ photocatalytic deposition of cesium lead bromide (CsPbBr 3 ) perovskite quantum dots on mesoporous TiO 2 -coated fluorine-doped tin oxide (FTO/TiO 2 ) electrodes. The mesoporous TiO 2 layer is used as a photocatalyst to promote the following: (1) the Pb deposition from a Pb 2+ aqueous solution and (2) the in situ Pb conversion into CsPbBr 3 pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The data are depicted in Figure . For laser powers higher than 150 μW, we have observed that fluorescence photobleaching takes place on the sample (fluorescence intensity reduction), as observed in other studies. …”
Section: Resultssupporting
confidence: 85%
“…The data are depicted in Figure . For laser powers higher than 150 μW, we have observed that fluorescence photobleaching takes place on the sample (fluorescence intensity reduction), as observed in other studies. …”
Section: Resultssupporting
confidence: 85%
“…Unlike the postsynthesis deposition of the NCs that results in lower compactness of the films, the in situ deposition of the NCs can be carried out by the two-step photocatalytic deposition of the NCs on mesoporous TiO 2 , where metallic Pb was first photocatalytically deposited on the FTO/TiO 2 substrate followed by photocatalytic reduction of Cs + to form the CsPbBr 3 NC films (Figure e) . Although lower quality MHP NC films with excess pinholes are obtained by different deposition methods, the film quality can be improved by annealing or mild heating in the presence of polar solvent vapors (Figure d,f) .…”
Section: Films With Perovskite Nanostructuresmentioning
confidence: 99%
“…Cesium lead bromide (CsPbBr 3 ) perovskite quantum dots (QD) have been used in various applications, including lightemitting devices, 1−3 photosensors, 4,5 and so on because of their high charge carrier mobility, high photoluminescence quantum yield (PLQY), and long carrier lifetime. 6 However, perovskite QDs have intrinsic chemical instability in the presence of moisture, heat, and ultraviolet (UV) radiation. 7 To overcome such instability, various kinds of passivation methods have been developed using polymers and crystal cross-linking materials like 2-aminoterephtahalic acid, phenyl ammonium iodide, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Cesium lead bromide (CsPbBr 3 ) perovskite quantum dots (QD) have been used in various applications, including light-emitting devices, photosensors, , and so on because of their high charge carrier mobility, high photoluminescence quantum yield (PLQY), and long carrier lifetime . However, perovskite QDs have intrinsic chemical instability in the presence of moisture, heat, and ultraviolet (UV) radiation .…”
Section: Introductionmentioning
confidence: 99%